Masdevallia luerorum (Orchidaceae: Pleurothallidinae), a new species from Costa Rica - Bogarín, Diego; Oses, Lizbeth; Smith, Christina M. (Lankesteriana: International Journal on Orchidology, 2017)
Masdevallia luerorum from the southern Pacific region of Costa Rica is described and illustrated. It resembles M. lata, but differs in the single flowered inflorescence, the shorter sepals, the broad and cylindrical sepaline tube, the smaller mentum beneath the column-foot, a smaller secondary mentum, a slight deflection between the two mentums, and the lip with marginal folds near the middle, apically rounded and conspicuously verrucose. Initial phylogenetic evidence indicated that Masdevallia nicaraguae is closely allied to M. luerorum. However, M. nicaraguae is distinguished by the white flowers suffused with fuchsia stripes toward the bases of sepals and the thick and triangular, shorter sepaline tails of the lateral sepals. Moreover, both species are isolated geographically.